THE EFFECT OF NATRIUM METABISULFITE IMMERSION AND DRYING TEMPERATURE FOR TAPAI FLOUR PRODUCTION - Aulia Brilliantina; Rizza Wijaya; Budi Hariono (University of Sultan Ageng Tirtayasa, 2021)
Tapai is one of the food ingredients that is processed into various food dishes and preferred. The shelf life of the tapai is easily damaged after being produced, because tapai has high moisture content, it is necessary to make an effort to extend the shelf life. The purpose of this research was to get the best treatment and to analyze the effect of different concentrations of Natrium Metabisulfite and drying temperatures on the quality of tapai flour. The method used in this study is an experimental research method with Completely Randomized Design (CRD). The first factor is concentration of natrium metabisulfite as much as 0 ppm, 1000 ppm, 2000 ppm, 3000 ppm and 4000 ppm. The second factor is the drying temperature of 45ºC, 55ºC, and 65ºC. The results of data analysis obtained the best treatment at concentration of 2000 ppm Natrium Metabisulfite with temperature of 55ºC, reducing sugar content of 4.35%, ash content of 1.5%, moisture content of 4.8%, yield 52.4% and value of the degree whiteness of 85.49.